2023
DOI: 10.1111/ijfs.16359
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of copper nanoparticles from Nigella sativa seed extract and evaluation of their antibacterial and antiobesity activity

Abstract: In this study, the copper nanoparticles were synthesized using various concentrations (5%, 6 %, 8%, and 10%) of Nigella sativa seed extracts, and their antibacterial and antiobesity effect was evaluated. The optimum particle size (98.23 nm) of nanoparticles was obtained at an extract concentration of 8%. FTIR results confirmed the functional groups responsible for copper ion reduction, The synthesized nanoparticles exhibited high antibacterial activity against Pseudomonas aeruginosa and Escherichia coli having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Igbokwe et al (2009) also reported higher serum HDL cholesterol in male rats (46.35 mg dL À1 ) as compared to female rats (45.20 mg dL À1 ) while decreasing the level of hepatic content. The lipid level was reduced in treated animal due to presence of alkaloids, glycoside, and flavonoids components in prepared herbal formulation (Kumar et al, 2023). The serum cholesterol level was decreased which directly triggers the activity of lecithin-cholesterol acyl transferase due to the presence of saponin in polyherbal formulation (Bharathi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Igbokwe et al (2009) also reported higher serum HDL cholesterol in male rats (46.35 mg dL À1 ) as compared to female rats (45.20 mg dL À1 ) while decreasing the level of hepatic content. The lipid level was reduced in treated animal due to presence of alkaloids, glycoside, and flavonoids components in prepared herbal formulation (Kumar et al, 2023). The serum cholesterol level was decreased which directly triggers the activity of lecithin-cholesterol acyl transferase due to the presence of saponin in polyherbal formulation (Bharathi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several plant extracts are used to prepare allopathic and western medicine to treat and cure multiple diseases, i . e ., thyroid, diabetes, pain relievers, migraine, and blood pressure medications (Kumar et al ., 2020a, 2020b; Kumar et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their effects were confirmed to occur via the AMP-activated protein kinase pathway [ 98 ]. Copper NPs synthesized from Nigella sativa seed extracts demonstrated potential antiobesity and antidiabetic effects by inhibiting the enzyme activities of lipase and α-amylase, respectively [ 99 ].…”
Section: Phytonanotherapy For Masld/mashmentioning
confidence: 99%
“…In the Dieng area, Wonosobo, Central Java, there is a plant commonly called Carica. Carica Dieng (Carica pubescens) belongs to the Caricaceae family [23]. Its area of origin is the Andean highlands of South America [24].…”
Section: Introductionmentioning
confidence: 99%